Duodenal Obstruction from Congenital Bands: An Unusual Cause of Pancreatitis. (1st December 1996) - Just, JD; Bailey, RJ
Abstract : Acute pancreatitis in children has many different causes. An unusual case of pancreatitis is presented, along with a review of some of the factors associated with pancreatitis in children. The probable pathogenesis of pancreatitis in this case is also discussed.